The McGraw-Hill handbook of distance learning - Chute, Alan G. 4 0 16; Thompson, Melody M.;Hancock, Burton W.; 5 (New York : McGraw-Hill, 1999)
Offers advice for organizations on how to implement distance learning programs, presenting a rationale for distance learning, looking at various technologies for the delivery of distance learning, and discussing program design, management and expansion, and other topics.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Distance education;Information technology;Computer-assisted instruction;Distance education;Information technology;Computer-assisted instruction. -- United States.;United States.;United States.;United States.;United States; 20; 2